Testing theories of job creation: does supply create its own demand? - Mikael Carlsson; Stefan Eriksson; Nils Gottfries (Center for Economic Studies and ifo Institute (CESifo), 2006)
Although search-matching theory has come to dominate labor economics in recent years, few attempts have been made to compare the empirical relevance of search-matching theory to efficiency wage and bargaining theories, where employment is determined by labor demand. In this paper we formulate an empirical equation for net job creation, which encompasses search-matching theory and a standard labor demand model. Estimation on firm-level data yields support for the labor demand model, wages and product demand affect job creation, but we find no evidence that unemployed workers contribute to job creation, as predicted by search-matching theory.
Keywords: E24; J23; J64; 330; Beschäftigungspolitik; Arbeitsmarkttheorie; Arbeitsnachfrage; Arbeitsplatzsuchmodell; Arbeitslosigkeit; Lohn